Reinfection Caused by SARS-CoV-2 - Navarro-Olivos, Efraín; Flores-Vargas, Gilberto; Gallardo-Luna, María de Jesús; Padilla-Raygoza, Nicolás; Díaz- Martínez, Daniel Alberto; Lara-Lona, Elia; Magos -Vazquez, Francisco Javier (Issues and Developments in Medicine and Medical Research Vol. 9, 2022)
In this chapter, we review the evidence of reinfection reported worldwide. Also, we describe the general aspects of SARS-CoV-2 and COVID-19. The evidence consists primarily of study cases, and a few are population studies. Studying reinfections presents difficulties primarily due to the technology and process required to verify that the case under study is true reinfection and not a prolonged permanence of the virus in the body. Reinfection seems a rare event so far. Nevertheless, on the surge of variants of concern, it may change. The study of reinfections is crucial to understanding the subsequent course of the COVID-19 pandemic.